Kemampuan penalaran matematis peserta didik dalam menyelesaikan soal literasi numerasi ditinjau dari gaya kognitif reflektif-impulsif - Rehan Muchammad Fadli Chusnudhin; Ahmad Farhan Ahshoni; Ahmad Arofi Nafsak; Kelvin Lutfi Permana; Anisa Fatwa Sari (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2023)
Mathematical reasoning is one of the five fundamental mathematical abilities that students need to master. The ability of mathematical reasoning is required by students to solve numeracy literacy problems. One of the factors influencing students' mathematical reasoning abilities is their reflective-impulsive cognitive style. This research aims to describe students' mathematical reasoning abilities in solving numeracy literacy problems in terms of the reflective-impulsive cognitive style. The research adopts a qualitative approach, with 6 students from class 9B at SMP Al Falah Ketintang Surabaya selected using purposive sampling. The research instruments include the MFFT cognitive style test sheet, numeracy literacy test sheet, and an interview guide that has been validated by three validators. Data analysis techniques involve data collection, data condensation, data presentation, and drawing conclusions. Based on the analysis and discussion, it is concluded that the mathematical reasoning abilities of students with a reflective cognitive style, particularly in the indicator of performing mathematical manipulations, are not yet well fulfilled. Similarly, the mathematical reasoning abilities of students with an impulsive cognitive style, especially in the indicator of constructing evidence and providing reasons/evidence for the correctness of the solution, are not yet well fulfilled. The mathematical reasoning abilities of students with both reflective and impulsive cognitive styles in solving numeracy literacy problems are more dominant in the moderate and low categories.